2019
DOI: 10.1002/chem.201900964
|View full text |Cite
|
Sign up to set email alerts
|

Improving Catalyst Activity in Hydrocarbon Functionalization by Remote Pyrene–Graphene Stacking

Abstract: Ac opperc omplex bearing an N-heterocyclic carbene ligand with ap yrene "tail" attached to the backbone has been prepared and supported on reduced graphene oxide (rGO). The free and supported copper materials have been employed as homogeneous and heterogeneous catalysts in the functionalization of hydrocarbonss uch as nhexane, cyclohexane, and benzene through incorporation of the CHCO 2 Et unit from ethyl diazoacetate. The grapheneanchored complex displays higherr eaction rates and induces higher yields than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…We have observed that this process is general and it has been experienced for other catalytic systems using graphene as support. [ 47–53 ] The catalytic activity of the molecular platinum complex improves when supported onto graphene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have observed that this process is general and it has been experienced for other catalytic systems using graphene as support. [ 47–53 ] The catalytic activity of the molecular platinum complex improves when supported onto graphene.…”
Section: Resultsmentioning
confidence: 99%
“…We have observed that this process is general and it has been experienced for other catalytic systems using graphene as support. [47][48][49][50][51][52][53] The catalytic activity of the molecular platinum complex improves when supported onto graphene. A common problem generally encountered in supported catalysis is the release of the catalytic active species into the solution during the reaction, known as the "boomerang effect".…”
Section: Catalytic Applicationsmentioning
confidence: 99%
“…Finally, in our first contribution to this field, in collaboration with the group of Mata, we have investigated the catalytic properties of a copper complex bearing an N-heterocyclic carbene ligand with a pyrene tag, both molecularly and non-covalently immobilized onto rGO (26-rGO, Scheme 21) [56] in the carbon-hydrogen bond functionalization by carbene insertion from ethyl diazoacetate, EDA (Scheme 21). The comparison of the homogeneous and heterogeneous catalysts was carried out using n-hexane, cyclohexane and benzene as substrates in reactions involving the transfer of the CHCO 2 Et group from EDA, employing a catalyst loading of 1.0 mol% and NaBAr F 4 as halide scavenger.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…It is worth noting that in most of those cases no significant changes were observed, demonstrating the stability of the graphene-modified solids during catalysis for different transformations and reaction conditions. Graphene oxide, in any of their variants (GO, rGO, TRGO, MRGO) was the support which remains unaltered in the case of catalysts 3, [29] 5, [32] 11 [39] and 13 [41] for cross-coupling reactions; 18 [48] for CÀ H bond oxidation, 19, [49] 21 [51] and 22 [52] for three-component reactions, 23 [53] for allylation reaction and 26-rGO [56] for carbene insertion into CÀ H bonds. There is only one exception, that of catalyst PdÀ DI@GO (12) [40] for which studies carried out by SEM demonstrated that the morphology of the GO changed during catalysis, affecting the agglomeration of the GO layers.…”
Section: Graphene-materials Deterioration During Catalysismentioning
confidence: 99%
See 1 more Smart Citation